Intellectual property infringement in fashion: insufficient enforcement and how blockchain may change the landscape - Lapatoura, Ioanna (2024)
Intellectual property infringement in fashion, or else the unauthorised copying of fashion designs that may enjoy trade mark, copyright or design law protections, is a rapidly growing global phenomenon. Despite current efforts to minimise it, design copying appears to be the fashion sector’s longstanding pandemic. Yet it is far from harmless, not just to fashion designers and their intellectual property (IP) rights, but also to countries’ innovation, creativity and economic growth. Despite the existence of IP protection and enforcement frameworks that fashion designers could rely upon against unauthorised uses of their works, infringers seem to be unaffected and in fact, continue to ‘free ride’ and capitalise on the efforts of fashion innovators. At the same time, customs and border enforcement authorities serve to detect and confiscate IP infringing products. However, the phenomenon persists, notwithstanding the efforts already being made to tackle this threat.